2001
DOI: 10.1074/jbc.m007730200
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of Nonspecific Lipid Transfer Protein and Sterol Carrier Protein x

Abstract: Nonspecific lipid transfer protein (nsLTP; also called sterol carrier protein 2) with a molecular mass of 13 kDa is synthesized as a larger 15-kDa precursor (pre-nsLTP) with an N-terminal 20-amino acid extension presequence, as well as with the peroxisome targeting signal type 1 (PTS1), Ala-Lys-Leu, at the C terminus. The precursor pre-nsLTP is processed to mature nsLTP by proteolytic removal of the presequence, most likely after being imported into peroxisomes. Sterol carrier protein x (SCPx), a 59-kDa branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 43 publications
(80 reference statements)
4
27
1
Order By: Relevance
“…By retention, stabilisation and presentation of fatty acid oxidation intermediates suitable for catabolism in the peroxisome, coupled to rejection of carnitine derivatives, SCP2 could significantly increase the efficiency of cellular fatty acid oxidation. One in vivo study has indicated that there is a pool of preSCP2 in the cytosol [9]. In this study we have not been able to distinguish any significant difference in activity of preSCP2 or mSCP2 towards fatty acyl carnitines in vitro, thus there is no basis for suspecting that the presence of a cytosolic concentration of preSCP2 will interfere with the uptake of fatty acyl carnitine derivatives by the mitochondrion.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…By retention, stabilisation and presentation of fatty acid oxidation intermediates suitable for catabolism in the peroxisome, coupled to rejection of carnitine derivatives, SCP2 could significantly increase the efficiency of cellular fatty acid oxidation. One in vivo study has indicated that there is a pool of preSCP2 in the cytosol [9]. In this study we have not been able to distinguish any significant difference in activity of preSCP2 or mSCP2 towards fatty acyl carnitines in vitro, thus there is no basis for suspecting that the presence of a cytosolic concentration of preSCP2 will interfere with the uptake of fatty acyl carnitine derivatives by the mitochondrion.…”
Section: Discussioncontrasting
confidence: 68%
“…The NR-BA assay was previously used to demonstrate the 2:1 binding of linoleoyl [16,34] between the isoforms. The presequence and PTS1 are thus implicated in regulating SCP2 localization [9,34]. The physiological relevance of the lack of LCFA-carnitine binding capacity of SCP2 may relate to the dual role of the peroxisome and the mitochondrion in fatty acid b-oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the rapid segmental mobility of the 20-amino acid N-terminal presequence on the NMR and X-ray time scale has led to the interpretation that these regions are unstructured, this does not necessarily exclude the presence of secondary structure elements within these mobile segments. On the contrary, Chou-Fasman modeling of the 20-amino acid N-terminal presequence suggests the presence of both α-helix and β-sheet structures therein (45). Likewise secondary structure prediction based on the program PHDsec suggests the presence of an α-helix in the presequence (46).…”
Section: Discussionmentioning
confidence: 99%
“…However, on the basis of secondary structure modeling of the 20-amino acid presequence (Figure 1), it has been suggested that the presequence contains a small α-helical element from amino acid −17 to −15 and a β-sheet from amino acid −8 to −3 (45). To begin to address this possibility and obtain molecular details of the structure of these polypeptide sequences, a series of proSCP-2 and SCP-2 N-terminal peptides was synthesized for secondary structure analysis by circular dichroism:…”
Section: Synthesis Of N-terminal Peptidesmentioning
confidence: 99%